Inheritance Studies of Morphological Characteristics in Okra (Abelmoschus esculentus L. Moench) Under Drought Conditions (Biological Sciences - PJSIR, 2007)
. The present studi es aimed at assessing th e inheritance pattern of morphological characteri stics i.e. days taken to flower, days taken to maturity, fresh fruit y i eld per pl ant , 100-seed weight and seed y ield per pl ant of okra (Abelmoschus esculentus L. Moen ch) under normal and water stress con d ition s to expl ore _droughUol erant genetic sources. Three gen otypes viz. DLPG x Parbhani Karanti , N o. 8 x Green Velvet and Parbh am Karant1 x Green Velvet were evaluated under n ormal (T l ) and drought (T2) condi t i on s to assess the trend of i nheritan ce. In Tl , week l y i rrigation was given an d in T2 th ree consecut i v e i rri gations were skipped out at now edn g and podd i n g stage. o respon se of water stress wa s observed i n heterosis, i n breedin g depressi on and poten ce ra.t 10 for days taken to matlln ty. However, the combi n at i ons exh i b i ted different i al beh avior for days taken to flower, fresh fn11t y i eld per plant,  100- seed weight and seed yie ld per plant of okra due to water stress.